THE INFLUENCE OF SOCIAL SUPPORT ON STUDENT LEARNINGEFFECTIVENESS IN ONLINE LEARNING: (CASE STUDY OF GUIDANCE AND COUNSELING DEPARTMENT) - Ahmad Sawali; Roy Hartono, Kaharuddin (Adisam Publisher, 2024)
This research aims to investigate the influence of social support on student learning effectiveness in the context of online learning, with a focus on students majoring in Guidance and Counselling. This study was conducted through a case study approach at a higher education institution. The main problem formulation includes an assessment of the level of social support felt by Guidance and Counseling students in online learning and its impact on their learning effectiveness. Apart from that, this research also aims to identify the types of social support that most influence student learning effectiveness, as well as examine the implications for the development of more effective support strategies. The research method used involved surveys, structured interviews and questionnaires for students in the Guidance and Counseling Department who were the focus of the study. It is hoped that the results of this research will provide a better understanding of the importance of social support in increasing student learning effectiveness in the online learning context, especially for students majoring in Guidance and Counseling. It is also hoped that the findings from this research can provide valuable input for the development of supporting strategies that are more effective in improving student academic achievement.